A selection of Marco Martos’s Poems - Arrizabalaga, Carlos (Mercurio Peruano, 2016)
Marco Martos’s poems explore human sensibility in different vital areas: love, friendship, relationships, nostalgia, death and how the time goes by, in a discourse full of paradoxes, with special attention to rhythm and symbolic images, and particularly all variety of colors.